PENGARUH KUALITAS MAKANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA FOOD JUNCTION CANTEEN UNIVERSITAS PELITA HARAPAN KARAWACI - ROSIANA SIANIPAR (JURNAL ILMIAH SIMANTEK, 2020)
Building customer satisfaction is a key priority for business success. Consequently, determining the factors that affectcustomer satisfaction is important. This research was designed to examine the effects of food quality and price on customersatisfaction in the Food Junction Canteen of Universitas Pelita Harapan Karawaci. The data were collected from 262respondents in the Food Junction Canteen of Universitas Pelita Harapan Karawaci. The collected data were analysed usingSPSS and structural equation modelling (SEM). The findings indicated that food quality has a significant positive effect oncustomer satisfaction. The result findings revealed that price have significant positive effects on customer satisfaction. Thesefindings provide useful suggestions and guidelines for the policy makers in the Food Junction Canteen in Universitas PelitaHarapan Karawaci and confirm the importance of the selected factors in affecting customer satisfaction.